The Effects of Oxytocin on Sexual Disorders - Nazari, Ali (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to investigate the effects of oxytocin on sexual function by reviewing evidence from both animal and human studies, with a focus on its physiological, neurochemical, and psychological mechanisms. Methods and Materials: The article employed a comprehensive narrative review of experimental and clinical research conducted between 2007 and 2023, including studies on animal models (notably Wistar rats) and human participants. The studies explored oxytocin’s effects through various administration routes (intraperitoneal injection, intranasal spray, and vaginal gel), utilizing both randomized controlled trials and observational methodologies. Parameters such as sexual behavior indices (e.g., mount latency, ejaculation latency), hormonal levels (oxytocin, cortisol, prolactin), subjective sexual function scores (e.g., FSFI, FSDS, SQOL-F), and physiological responses (e.g., blood flow, erectile function, vaginal pH) were evaluated across multiple interventions. Findings: Animal studies demonstrated that oxytocin, alone or in combination with adrenergic modulators, significantly enhanced sexual behaviors and reproductive parameters in male rats. In ischemia-reperfusion models, oxytocin improved spermatogenesis without altering sex hormone levels. Human trials revealed that intranasal and vaginal oxytocin improved sexual desire, arousal, lubrication, and satisfaction in women with sexual dysfunction, including postmenopausal subjects. In women treated with SSRIs, oxytocin levels correlated positively with sexual function scores. However, some studies indicated placebo-level or inconsistent results in healthy individuals. Despite oxytocin’s notable increase in subjective arousal and hormonal changes (e.g., epinephrine elevation), measurable behavioral effects varied. Conclusion: Oxytocin plays a multifaceted role in modulating sexual behavior and function through central and peripheral mechanisms, including neural activation, hormonal modulation, and emotional regulation. While the evidence supports its therapeutic potential in specific sexual dysfunctions, especially stress- and hormone-related cases, further studies are needed to optimize dosage, delivery methods, and identify individual response variability.